Association of new obesity markers with symptoms of depression: analysis of a 4-year Peruvian national survey - Iturregui Paucar, Cori Raquel (2023)
Introduction: Although body mass index (BMI) and waist circumference (WC) are the most commonly used obesity markers in clinical practice regarding depression, some studies suggest that other obesity markers such as waist-to-height ratio (WHtR), a body shape index (ABSI), body roundness index (BRI), and conicity index (CI) may be more accurate in identifying patients with depression. Objective: To determine the relationship between different markers of obesity and the presence of symptoms of depression. Methods: Analytical cross-sectional study. A secondary analysis was conducted on the Demographic and Family Health Survey (ENDES) from 2018 to 2021. The main variable of the present study was the depression score. Numerical variables were presented as mean and confidence interval at 95 % (CI 95 %). A generalized linear model of the Gaussian family and Identity link function was performed to evaluate the strength of association between the variables of interest. Results: The average depression score in the study population was 2.61 (95 % CI 2.56–2.65). In the multivariable analysis, the depression score increased for each unit that increased the BMI by 0.011 points (β = 0.011; 95 % CI 0.002–0.020), the WHtR by 0.207 points (β = 0.207; 95 % CI 0.145–0.267), the ABSI by 0.158 points (β = 0.158; IC95% 0.047–0.269), the BRI by 0.096 points (β = 0.096; IC95% 0.069–0.122), and the CI by 0.010 points (β =0.010; IC95% 0.004–0.016). There was no statistically significant association for WC. Conclusions: The WHtR may be a better marker of obesity for identifying patients with depressive symptoms compared to other markers.